Ovarian borderline tumor presenting as ovarian torsion in a 17-year-old patient: a case report - Vicente, Ana Patrícia (J Med Case Rep, 2021)
BACKGROUND: Ovarian torsion is a gynecological surgical emergency whose diagnosis remains a challenge. Torsion occurs most frequently in women of reproductive age. It is usually associated with the presence of benign masses in the ovary, as malignant tumors are less frequent and less prone to undergo torsion. CASE PRESENTATION: We report the case of a 17-year-old Caucasian patient who presented to the emergency department with lower abdominal pain. Ultrasonography evaluation revealed a unilateral ovarian lesion, 11.2 cm, with features suspicious for malignancy and torsion. The patient was referred for surgical torsion treatment and underwent unilateral salpingo-oophorectomy. The pathology report confirmed a serous borderline ovarian tumor with torsion. CONCLUSIONS: Malignant ovarian torsion in pediatric age groups is rare. Ultrasound examination should be recognized as a powerful tool for diagnosis and management, especially when performed by an experienced ultrasonographer.